2019
DOI: 10.2217/bmm-2018-0309
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Estimated Whole Blood Viscosity with Hemodynamic Parameters and Prognosis in Patients with Heart Failure

Abstract: Aim: We aimed to investigate the association of estimated whole blood viscosity (WBV) with hemodynamic parameters and prognosis in patients with heart failure with reduced ejection fraction. Materials & methods: Total of 542 patients were included and followed-up for median 13 months. Results: The WBV parameters had negative relationship with right atrium pressure and positive correlation with cardiac index. The WBV parameters were found to be independent predictors of composite end point (CEP) and all-cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Notably, viscosity decreased after hydration therapy, but hyperviscosity recurred when hydration therapy was discontinued [11]. Our study population showed a more stable clinical condition before surgery, as represented by ASA physical status I or II, compared to the patients in previous studies [10,11,13,20,30]. During RALP surgery, we encountered no hemodynamic instability that required aggressive fluid or blood product transfusion therapy.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Notably, viscosity decreased after hydration therapy, but hyperviscosity recurred when hydration therapy was discontinued [11]. Our study population showed a more stable clinical condition before surgery, as represented by ASA physical status I or II, compared to the patients in previous studies [10,11,13,20,30]. During RALP surgery, we encountered no hemodynamic instability that required aggressive fluid or blood product transfusion therapy.…”
Section: Discussionmentioning
confidence: 50%
“…Many clinical studies have suggested that elevated WBV is associated with the development of cardiovascular and cerebrovascular diseases [10,11,13,30]. In patients with mitral annular calcification, higher WBV was predictive of pathologic mitral annulus.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In their study De Simone et al evaluated WBV with a simple, costless equation using total protein and HCT levels at different shear rates [8]. The prognostic value of estimated WBV calculated by this formula has been demonstrated in many studies for cardiovascular diseases [11][12][13][14][15]. In our study, we also preferred to use this formula to evaluate WBV.…”
Section: Discussionmentioning
confidence: 92%
“…Notably, erythrocytosis may result in symptoms of hyperviscosity in patients with heart failure [ 38 ], but these conditions rarely appear until HTO is >65% and are related to its progressive increase and not to its elevated level per se. On the other hand, it is possible that compensated erythrocytosis manifests in these patients when HTO values (even those greater than 70%) remain stable for a long time, while decompensated erythrocytosis is generated when these values are not stable or increase progressively [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%